Across the Isles: The Transnational Lordship of the Mortimer Earls of March and Ulster 1368-1398 - McDonagh, Patrick Bernard (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2023)
This thesis offers an original examination of a transnational aristocratic lordship which spanned the worlds of late fourteenth century Ireland, Wales, and England. The composite lordship of the Mortimer earls of March and Ulster was one of the greatest of its day. Nonetheless, it has been overlooked by historians. This thesis provides the first detailed study of the Mortimer composite earldom in the late fourteenth century that embraces the entirety of the Mortimer inheritance and exploits a rich though neglected seignorial archive. Its principal argument is that the Mortimer lordship of the late fourteenth century can only be understood in a wider transnational setting that takes account of the entire lordship across Wales, Ireland, and England. This framework has built upon two previous schools of historiography, the `new British history' approach as developed in the works of R.R. Davies and Robin Frame in the 1980s and 1990s, and the `Plantagenet empire' model as propounded by Peter Crooks, David Green, and W. Mark Ormrod in the last decade. Both schools have attempted to approach the history of late medieval Britain and Ireland by transcending the boundaries of national historiographies. To uncover the nature of this transnational lordship, the thesis explores the administration of the Mortimer lordship, the affinities surrounding the earls, and examines the significance of their military campaigns in the lordship of Ireland. These studies into the administrative, documentary, and military cultures of the Mortimer composite earldom reveal a vigorous transnational lordship capable of effectively exercising its influence on both sides of the Irish Sea.
APPROVED
Keywords: Transnational; Medieval; Ireland; Wales; England; Lordship; Aristocratic